Afasia e enunciação: estudo das manifestações linguísticas de um sujeito com afasia em convivência grupal - Barros, Gabriel Rovadoschi (2021)
This study is born of the encounter of the author (psychologist) with the disturbs of communication problematic, especially aphasias, who cared about understanding how a person with aphasia is made subject in the enunciation being recognized by your interlocutors. The present study aims at the effects of aphasia on the production/interpretation – verbal and non-verbal – of subjects in this condition of language. The general objective was to investigate linguistics manifestations of a single subject with aphasia emerging from a living group which involves other subjects with and without aphasia. Thus, sought to identify and analyze the “inner speech” produced by a subject with aphasia in the group, as well as to discuss the effects of the Interdisciplinary Group of Coexistence (GIC) in the linguistics expressions of the referred subject. The present study adopts a qualitative, exploratory methodological approach, using video footage from a Permanent Database (BDP-GIC), allowing a study case of one of the subjects with aphasia, participant of the group (UN). The data analysis took place according to the theorical contributions of a enunciative approach of Linguistics, specially the benvenistean. Through the presentation of three dados-achados (produced on GIC), it was possible to highlight enunciative elements that corroborated in subjective manifestations of UN’s language, evidencing the trinitary structure (I-you-he) of the formal apparatus of enunciation and the signification domains affected by the aphasia and bypassed by UN. Therefore, GIC affirmed itself as a productive place on the interpretation of and to the singular expression of the subject, that is, locus for UN to position itself in and through language, promoting meanings, even, about his relationship with aphasia itself. Therefore, it was possible to reaffirm the coexistence of an interdisciplinary way in the longitudinal care of subjects with aphasia, valuing the appropriation of linguistics theories to steer the clinic practice with these subjects, mainly, in the group context that expands the opportunities of verbal and social interaction.